(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study explores the intricate relationship between corporate governance mechanisms and their influence on the performance metrics of banks, considering different ownership structures in the Indian banking sector. In light of the economic reforms and heightened regulatory scrutiny post the 1990s, this study investigates whether the changes in governance practices have substantially affected the performance outcomes of banks in terms of profitability, risk management, and operational efficiency.